2003
DOI: 10.1902/jop.2003.74.6.844
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Porphyromonas gingivalis. Serotypes to Pocket Epithelium

Abstract: This study indicates that the presence and type of capsule have a significant influence on the initial adhesion of P. gingivalis to human periodontal pocket epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 24 publications
1
29
0
8
Order By: Relevance
“…This assay was previously used to assess the hydrophobicity of P. gingivalis strains. It was shown that strains ATCC 33277 and 381 are hydrophobic and do not make significant amounts of capsular polysaccharide (16,82), and indeed, we found that these strains partitioned into hexadecane by approximately 90%. Increased partitioning was not observed in the respective PG0106 mutants.…”
Section: Isolation Of the Pg0106 Mutantsupporting
confidence: 67%
See 2 more Smart Citations
“…This assay was previously used to assess the hydrophobicity of P. gingivalis strains. It was shown that strains ATCC 33277 and 381 are hydrophobic and do not make significant amounts of capsular polysaccharide (16,82), and indeed, we found that these strains partitioned into hexadecane by approximately 90%. Increased partitioning was not observed in the respective PG0106 mutants.…”
Section: Isolation Of the Pg0106 Mutantsupporting
confidence: 67%
“…6B). As noted above, it has been shown that strains ATCC 33277 and 381 are hydro- phobic and do not make significant amounts of capsular polysaccharide (16,82). India ink staining of these two strains is shown in Fig.…”
Section: Isolation Of the Pg0106 Mutantmentioning
confidence: 74%
See 1 more Smart Citation
“…The K-antigen capsule of P. gingivalis is considered a key virulence factor (52). Encapsulated strains disseminate, causing a spreading type of infection in mice, with recovery from blood, spleen, and kidneys after subcutaneous inoculation, while K-antigen null strains typically result in localized abscesses and are significantly less virulent in soft tissue destruction (17,31). Also, it was recently reported that mice immunized with purified K-antigen capsule were protected against oral bone loss when challenged with P. gingivalis (24).…”
mentioning
confidence: 99%
“…Also, it was recently reported that mice immunized with purified K-antigen capsule were protected against oral bone loss when challenged with P. gingivalis (24). With regards to interaction with the human host, the presence and type of capsule has been found to influence the initial adhesion of P. gingivalis to human periodontal pocket epithelial cells (17) and to reduce the immune response of human gingival fibroblasts (7). Furthermore, the majority of clinical P. gingivalis strains isolated from patients with destructive periodontal disease synthesize K-antigen capsule (30), indicating a link between the disease state and the proliferation of an encapsulated phenotype.…”
mentioning
confidence: 99%